(untitled) (Research, Society and Development, 2021)
Continuing education has become one of the bets of education for teacher professional development, considering the rapid changes that occur in the educational context that require professionals to invest in their own training. This article refers to a section of the bibliographic research carried out to support a study in progress at the Master’s level and proposes to answer the following problems. What is the relevance of continuing education for the development of teachers’ pedagogical practices? And what is the contribution of the reflective teacher theory in continuing education? The methodology was qualitative in nature, based on the literature review method with the support of bibliographic and exploratory research and, for the analysis of the information extracted from readings in thirty articles that discussed the theme in question. Support was sought for the content analysis method. Thus, the study’s methodological path allowed to go to reliable sources that require the researcher’s greater critical understanding of already existing reports. Our conclusion, according to the thought of the studied authors: shows that: a) being in a constant training process implies personal investment and is a contribution to the construction of the teaching identity; b) continuing education is a personal and institutional need that accompanies the teacher’s professional trajectory; c) The continuous training process is not characterized as recycling, or is not limited to a simple update, training or qualification of the teacher; d) Continuing education requires lifelong learning; e) This training must be seen as a mechanism for permanent reflexive training. Therefore, the relevance of continuing education is in the expansion of knowledge and the need for reflection on teaching and learning.